Advances on the roles of circular RNA in breast cancer - HE Xiao, HU Wei-jie, LYU Wen-chang, REN Yu-ping, WU Min, WU Yi-ping, ZHANG Qi (Jichu yixue yu linchuang, 2022)
Circular RNA (circRNA) is a kind of non-coding RNA with circular structure and is found in a variety of cell types. CircRNA is characterized by diversity, specificity, conservatism and stability. As an emerging non-coding regulatory molecules, circRNA can regulate the proliferation and metastasis of breast cancer (BC) mainly through the mechanism of competitive endogenous RNA, and is involved in a variety of chemotherapy resistance and affect the efficacy. Elucidating the functions and mechanisms of circRNA in BC may provide novel and effective strategies for the diagnosis and treatment of BC.